National Working Group Meeting on ALK diagnostics in lung cancer. (April 2014) - Cooper, Wendy; Fox, Stephen; O'Toole, Sandra; Morey, Adrienne; Frances, Glenn; Pavlakis, Nick; O'Byrne, Kenneth; Dettrick, Andrew; Leong, Trishe; Rathi, Vivek; Spagnolo, Dominic; Hemmings, Chris; et al.
Abstract: The global landscape of molecular testing is rapidly changing, with the recent publication of the International Association for the Study of Lung Cancer (IASLC)/College of American Pathologists (CAP) guidelines and the ALK Atlas. The IASLC/CAP guidelines recommend that tumors from patients with non‐small cell lung cancer (NSCLC) be tested for ALK rearrangements in addition to epidermal growth factor receptor (EGFR) mutations. The spur for this recommendation is the availability of novel therapies that target these rearrangements. This article is based on coverage of a Pfizer‐sponsored National Working Group Meeting on ALK Diagnostics in Lung Cancer, held around the 15th World Lung Cancer Conference, in Sydney on October 31, 2013. It is based on the presentations given by the authors at the meeting and the discussion that ensued. The content for this article was discussed and agreed on by the authors.